2021
DOI: 10.1097/grf.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Disparities Using Telehealth Approaches for Postdelivery Preeclampsia Care

Abstract: The management of hypertensive disease of pregnancy presents an ongoing challenge after patients are discharged from delivery hospitalizations. Preeclampsia and other forms of postpartum hypertension increase the risk for severe maternal morbidity and mortality in the postpartum period, and both hypertension and its associated adverse events disproportionately affect black women. With its ability to transcend barriers to health care access, telemedicine can facilitate high-quality postpartum care delivery for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Black patients suffer higher rates of preeclampsia, preeclampsia-related readmission, and subsequent long-term cardiac disease. 28 , 29 , 30 Postpartum, Black women have a slower decrease in blood pressure over a 6-week remote blood pressure monitoring program compared with White women, 29 and overall are more likely to be diagnosed with hypertension earlier in life and suffer from more significant morbidity related to hypertension, with 4 to 5 times greater mortality compared with non-Hispanic White Americans. 31 …”
Section: Opportunities To Reduce Racial Inequities In Carementioning
confidence: 99%
See 1 more Smart Citation
“…Black patients suffer higher rates of preeclampsia, preeclampsia-related readmission, and subsequent long-term cardiac disease. 28 , 29 , 30 Postpartum, Black women have a slower decrease in blood pressure over a 6-week remote blood pressure monitoring program compared with White women, 29 and overall are more likely to be diagnosed with hypertension earlier in life and suffer from more significant morbidity related to hypertension, with 4 to 5 times greater mortality compared with non-Hispanic White Americans. 31 …”
Section: Opportunities To Reduce Racial Inequities In Carementioning
confidence: 99%
“…In another study, >20% of Black women who missed an in-office appointment were initiated on medications via remote monitoring. 16 , 28 , 30 …”
Section: Opportunities To Reduce Racial Inequities In Carementioning
confidence: 99%
“…Another technology-based intervention is mHealth, which refers to the use of mobile devices or Bluetooth technology in public health practice. mHealth may be particularly helpful among those with limited access to health care, as it enables health monitoring or education to occur virtually, overall reducing logistical barriers 89. Postpartum remote blood pressure monitoring through Bluetooth systems linked to clinics for individuals with HDP have high retention rates and show improvements in postpartum visit attendance 65–69.…”
Section: Interventions To Improve Postpartum Monitoring Screening And...mentioning
confidence: 99%
“…mHealth may be particularly helpful among those with limited access to health care, as it enables health monitoring or education to occur virtually, overall reducing logistical barriers. 89 Postpartum remote blood pressure monitoring through Bluetooth systems linked to clinics for individuals with HDP have high retention rates and show improvements in postpartum visit attendance. [65][66][67][68][69] Many individuals report being satisfied with addressing health concerns at home rather than the clinic, which may be particularly burdensome among those with limited transportation or childcare.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
“…38 , 39 Studies have shown promising results in this regard. 40 43 For example, a randomized control trial for postpartum hypertension shows that black women in the postpartum telehealth group had more than 90% utilization of services compared to 33% in the traditional in-person group. 40 Furthermore, evidence suggests that patients value having telehealth as an option.…”
Section: Introductionmentioning
confidence: 99%